The role of nuclear receptors in metabolic homeostasis and disease: From molecular mechanisms to drug discovery - Fangfang He; Haomeng Wu; Feilong Zhao; Xinxin Liu; Qin Yang; Shiquan Zhou; Tianling Xu; Jing Xu; Shuai Wang; Denglang Zou (Pharmacological Research)
Nuclear receptors (NRs) are a superfamily of ligand-dependent transcription factors that serve as pivotal regulators of gene expression in response to hormonal, metabolic, and environmental cues. They exert transcriptional control through complex interactions with co-regulators, thereby influencing gene networks involved in metabolic regulation, cell signaling, immune modulation, and homeostatic maintenance. Dysregulation of NR activity has been implicated in the pathogenesis of various metabolic and inflammatory conditions through altered gene expression and signaling cascades. This review provides an integrated overview of NR structural features and classification, elucidates their mechanisms of action in gene regulation and metabolic balance, and explores their dual roles in both physiological and pathological contexts. We further examine recent advances in NR-targeted drug discovery, including structure-based drug design, chemical biology approaches, and AI-assisted ligand development. Finally, we highlight multidisciplinary perspectives and emerging directions for NR research within the framework of precision medicine.